2015
DOI: 10.1007/s10815-015-0494-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anti-Müllerian hormone (AMH) and bone morphogenetic protein 15 (BMP-15) on steroidogenesis in primary-cultured human luteinizing granulosa cells through Smad5 signalling

Abstract: AMH and BMP-15 by interacting with FSH affect the production of estradiol and progesterone from cultured luteinizing-granulosa cells possibly via Smad5-protein phosphorylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 59 publications
4
19
0
2
Order By: Relevance
“…Another explanation for the presence of AMH in luteal cells may be that it exhibits a role in the local regulation of progesterone production in the corpus luteum. This assumption is supported by the study of Prapa et al [ 45 ], who reported that AMH exposure of luteinized human granulosa cells in vitro, decreased basal progesterone production. AMH is a member of the transforming growth factor B (TGFB) superfamily, that further includes bone morphogenetic proteins (BMPs), activins, inhibins and growth and differentiation factor 9 (GDF9).…”
Section: Discussionsupporting
confidence: 54%
“…Another explanation for the presence of AMH in luteal cells may be that it exhibits a role in the local regulation of progesterone production in the corpus luteum. This assumption is supported by the study of Prapa et al [ 45 ], who reported that AMH exposure of luteinized human granulosa cells in vitro, decreased basal progesterone production. AMH is a member of the transforming growth factor B (TGFB) superfamily, that further includes bone morphogenetic proteins (BMPs), activins, inhibins and growth and differentiation factor 9 (GDF9).…”
Section: Discussionsupporting
confidence: 54%
“…Reduction of estradiol concentration over the controls and BMP15 treated groups on day 21 maybe due to the differentiation of these cells. Our observations correspond to Prapa et al (2015) who found that BMP15 could reduce basal estradiol levels in human granulosa cells; however, Costa et al (2004) showed that levels of estradiol considerably decreased in the follicles with mature oocytes compared to the follicles with immature oocytes. We conclude that FF derived MSCs are a structural portion of the ovarian tissue, whether from OSE or from the cortical zone of the ovary.…”
Section: Discussionsupporting
confidence: 91%
“…AMH is produced by the ovarian granulosa cells and supports the follicular growth [4]. Effect of AMH and BMP-15 on estradiol and progesteron production in primarycultured human luteinizing granulosa cells was reported [5]. BMP-15 level in follicular fluid has been demonstrated to associate with oocyte and embryo quality [6].…”
Section: Introductionmentioning
confidence: 99%